Analysis of demographics and treatment outcomes for gastrointestinal leiomyosarcoma based on the SEER database - Yanan Bao; Xudong Yang; Quanming Zhao; Wenliang Li (Scientific Reports)
Abstract Knowledge of patients with gastrointestinal leiomyosarcoma (GILMS) is lacking. In this study, we aimed to clarify the disease features and prognosis of GILMS based on the Surveillance, Epidemiology, and End Results database. The clinicopathological, treatment, survival, and prognostic data of GILMS from 2000–2020 were retrieved. Appropriate statistical approaches were used to evaluate demographic characteristics and survival outcomes. A total of 479 individuals with GILMS met the screening criteria. The median age of patients was 64 (15–90) years. Only 7.9% of these cases were diagnosed with lymph node metastasis. T2 or higher primary tumor extension was diagnosed in 78.1% of the patients. The 5-year cancer-specific survival (CSS) of patients who had and had not undergone surgery was 66.5% and 0%, respectively. Multivariate Cox proportional hazards analysis based on overall survival and CSS showed that female sex was a significant independent protective factor. Significant independent risk factors included age 65–79, age ≥ 80, poor differentiation, T2 and higher T stage, distant metastasis, and no surgery. Neither chemotherapy nor radiotherapy influenced survival or prognosis. This comprehensive analysis underscored the necessity of surgical excision for prolonging survival times and highlighted the urgent need to explore effective systematic treatments.